Short report: Natural hybrid between Anopheles kleini and Anopheles sinensis - Joshi D. (2014)
While analyzing wild mosquitoes caught in Paju, South Korea, we identified one egg-laying hybrid female between Anopheles kleini and Anopheles sinensis. Additional evidence was obtained by identifying several F1 progeny and conducting self-crossing between them. Sequencing of mitochondrial cytochrome c oxidase subunit 1 sequence suggested that the maternal origin of the female should be An. sinensis. Additionally, observation of only two distinct genotypes of F1 progeny (double band, hybrid type, and single-band An. sinensis type) more closely resembled a situation of natural back-crossing between a hybrid female and male An. sinensis. Results of self-crossing between F1 progeny was impaired and yielded abnormally low larval hatchings (3.7%). Overall, the observation of 1 female from 658 caught-wild mosquitoes indicated possible natural hybridization among members of the Hyrcanus group from South Korea. Copyright © 2009 by The American Society of Tropical Medicine and Hygiene.